2022
DOI: 10.1021/acschemneuro.1c00849
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Neuroprotective Agents Based on a 5-(4-Pyridinyl)-1,2,4-triazole Scaffold

Abstract: Parkinson's disease (PD) is characterized by the death of dopaminergic neurons. The common histopathological hallmark in PD patients is the formation of intracellular proteinaceous accumulations. The main constituent of these inclusions is alpha-synuclein (α-syn), an intrinsically disordered protein that in pathological conditions creates amyloid aggregates that lead to neurotoxicity and neurodegeneration. The main goal of our study was to optimize our previously identified α-syn aggregation inhibitors of 5-(4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The misfolded proteins are generally considered “low druggable” targets, as they lack specific ligand-binding sites that efficiently establish strong binding with inhibitors or modulators. However, there are recently developed synthetic and natural small molecules that inhibit α-Syn aggregation and fibril formation in cell-based assays [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. These therapeutics are generally defined as disaggregators and might be characterized by a distinct mode of action.…”
Section: Introductionmentioning
confidence: 99%
“…The misfolded proteins are generally considered “low druggable” targets, as they lack specific ligand-binding sites that efficiently establish strong binding with inhibitors or modulators. However, there are recently developed synthetic and natural small molecules that inhibit α-Syn aggregation and fibril formation in cell-based assays [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. These therapeutics are generally defined as disaggregators and might be characterized by a distinct mode of action.…”
Section: Introductionmentioning
confidence: 99%
“…Triazole-based compounds are now under study for the treatment of a variety of central nervous system (CNS) diseases. The study of Gitto et al revealed 1,2,4-triazole-based compounds could inhibit α-syn aggregation to prevent Parkinson’s disease [ 19 ]. Wu et al worked on 1,2,4-triazole derivatives and found a series of anticonvulsant compounds by using epilepsy models during both in vivo and in vitro studies [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, SC-D and ZPD-2 have been used as scaffolds to rationally design variants with enhanced activity or pharmacological properties [ 340 , 341 ]. More recently, SC-D and ZPD-2 chemical scaffolds were used to generate a library of 34 different compounds obtained through a similarity-based virtual screening filtered to contain exclusively molecules with good drug-like properties [ 342 ]. In vitro studies confirmed the inhibitory capacity of MeSC-04 (an SC-D derivate) against α-Syn aggregation.…”
Section: New Therapies: Modulating α-Synuclein Aggregationmentioning
confidence: 99%
“…In vitro studies confirmed the inhibitory capacity of MeSC-04 (an SC-D derivate) against α-Syn aggregation. Computational analysis using two different α-Syn recombinant fibrils (PDB: 2N0A and 6FLT) suggested that MeSC-04 established Van der Waals contacts and hydrogen bonds with the α-Syn region comprising residues from A53 to V74 [ 342 ].…”
Section: New Therapies: Modulating α-Synuclein Aggregationmentioning
confidence: 99%